EDUCATIONAL OPPORTUNITIES OF TRAINING AND PRODUCTION PRACTICES IN ENVIRONMENTAL FORMATION CONSCIOUSNESS OF A FUTURE TEACHER OF BIOLOGY - Yu.O. Saunova (Academy of Cognitive and Natural Sciences, 2022)
The article is devoted to the analysis of the development of the possibility practice in ecological sense forming of future biology school-teachers.